2007
DOI: 10.1097/01.mlr.0000254574.23418.f6
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antidepressant Treatment Among Privately Insured Patients Diagnosed With Depression

Abstract: Background-Antidepressants are effective in treatment of depression, but poor adherence to medication is a major obstacle to effective care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
112
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 36 publications
10
112
2
4
Order By: Relevance
“…In one study reported that adherent subjects had a higher level of satisfaction with their physicians, with 87% indicating "excellent" or "very good," while only 60% of the nonadherent subjects indicated this level of satisfaction [21,22]. Unawareness of nature of depression disorder and adherence to treatment regimen has significantly influenced (p=0.49, t-test) mean drug attitude inventory scores in our study.…”
Section: Discussionmentioning
confidence: 58%
“…In one study reported that adherent subjects had a higher level of satisfaction with their physicians, with 87% indicating "excellent" or "very good," while only 60% of the nonadherent subjects indicated this level of satisfaction [21,22]. Unawareness of nature of depression disorder and adherence to treatment regimen has significantly influenced (p=0.49, t-test) mean drug attitude inventory scores in our study.…”
Section: Discussionmentioning
confidence: 58%
“…[38] Younger patients have a stronger negative bias towards issues such as weight gain, sexual dysfunction and dissatisfaction with the physician. [39,40] We also demonstrated that the treatment period has a definite influence on the MPR and patient compliance. We found that patients were prescribed an oversupply of AD during the first month of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have found mixed effects for the impact of disease burden on medication adherence, with some finding improved adherence in patients with greater comorbidity, 36,37 and others finding no effect or decreased adherence. 33,[38][39][40] There was a strong association between provider type and early adherence to antidepressants. Patients who received their antidepressants from psychiatrists were more likely to refill their antidepressants than those treated in primary care.…”
Section: Discussionmentioning
confidence: 99%